2004
DOI: 10.1107/s0907444904010492
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and X-ray diffraction analysis of insect-cell-derived IL-22

Abstract: Interleukin-22 is a potent mediator of cellular inflammatory responses. Crystals of interleukin-22 expressed in Drosophila melanogaster S2 cells (IL-22Dm) have been grown from polyethylene glycol solutions. To obtain crystals suitable for X-ray diffraction analysis required the separation of different IL-22Dm glycosylation variants and the inclusion of the detergent cetyltrimethylammonium bromide (CTAB) in the crystallization experiments. The crystals belong to space group P2(1), with unit-cell parameters a = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Structural studies on glycosylated IL-22, which contained 6 molecules in the asymmetric unit, have identified considerable conformational variability in the IL-10R2 binding site on IL-22 supporting this hypothesis (35,36). Furthermore, an anti-IL-22 antibody has been shown to increase the high affinity IL-22⅐IL-22R1 interaction, apparently by inducing conformational changes in the IL-10R2 binding site that are subsequently transmitted to the high affinity IL-22R1 binding site (37).…”
Section: Il-10r1 Induced Conformational Changes In the Il-10r2mentioning
confidence: 91%
“…Structural studies on glycosylated IL-22, which contained 6 molecules in the asymmetric unit, have identified considerable conformational variability in the IL-10R2 binding site on IL-22 supporting this hypothesis (35,36). Furthermore, an anti-IL-22 antibody has been shown to increase the high affinity IL-22⅐IL-22R1 interaction, apparently by inducing conformational changes in the IL-10R2 binding site that are subsequently transmitted to the high affinity IL-22R1 binding site (37).…”
Section: Il-10r1 Induced Conformational Changes In the Il-10r2mentioning
confidence: 91%
“…[19][20][21][22]26,29 All these hexacoordinated Ni(II) compounds crystallize in centrosymmetric space groups and the central Ni(II) is situated on an inversion center. In two of the compounds including 1 the metal exhibits a {NiO 6 } coordination sphere while in [Ni(Im) 6 ](4-nba) 2 .2H 2 O (Im = imidazole) the central metal is bound to six Ndonor ligands.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] The available literature on transition metal 4-nitrobenzoates especially Ni(II) is restricted to a few structure reports. [19][20][21][22] In view of this, we have initiated a systematic study of the chemistry of the transition metal 4-nitrobenzoates. In this paper we report on the synthesis, properties and structure of a new Ni(II) compound containing a free 4-nitrobenzoate (4-nba) and a comparative study of seven different nickel 4-nitrobenzoates.…”
Section: Introductionmentioning
confidence: 99%
“…1a). Mass spectroscopy analysis revealed that hexasaccharides (two N-acetyl glucosamines, three mannoses, and one fucose) are attached to the IL-22 protein expressed in D. melanogaster [56]. However, only glycosylation at Asn54 and Asn97 position was observed in the DM IL-22 crystal structure [25].…”
Section: Il-22 Structuresmentioning
confidence: 99%
“…The secondary structures features are shown as found in the IL-22 crystal structure (PDB ID 1M4R [8]). The potential IL-22 [25,56] and IL-19 [24] glycosylation sites are contoured by double lines. b A phylogram tree extract from this alignment.…”
Section: Three-dimensional Structure Considerationsmentioning
confidence: 99%